2004
DOI: 10.1021/jp048939k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Reactions of Stable Oxametallacycles from Styrene Oxide on Ag(111)

Abstract: Styrene oxide undergoes an activated ring opening on Ag(111) at temperatures above 200 K. The product of this reaction is a stable oxametallacycle intermediate. The structure of this species has been obtained by density functional theory calculations and the computed vibrational spectrum is consistent with the experimental spectrum obtained using high-resolution electron energy loss spectroscopy. The oxametallacycle formed by ring-opening styrene oxide is structurally analogous to that previously observed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
33
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 30 publications
8
33
0
Order By: Relevance
“…This approach permits consistent comparison of the barriers for reactions of different oxametallacycle species on different surfaces. The peak shapes for reaction of epoxybutenederived and styrene oxide-derived oxametallacycles at higher temperatures on Ag(111) and (110) surfaces are consistent with first order processes [5,8,9,24], but those for EO-derived oxametallacycles are less consistent owing to the procedures for isolating these peaks from the molecular state, as noted above. Nevertheless, the barriers determined are consistent with DFT calculations and previous results on the (111) surface.…”
Section: Ethylene Oxide Adsorption On Clean Ag(110)mentioning
confidence: 62%
See 4 more Smart Citations
“…This approach permits consistent comparison of the barriers for reactions of different oxametallacycle species on different surfaces. The peak shapes for reaction of epoxybutenederived and styrene oxide-derived oxametallacycles at higher temperatures on Ag(111) and (110) surfaces are consistent with first order processes [5,8,9,24], but those for EO-derived oxametallacycles are less consistent owing to the procedures for isolating these peaks from the molecular state, as noted above. Nevertheless, the barriers determined are consistent with DFT calculations and previous results on the (111) surface.…”
Section: Ethylene Oxide Adsorption On Clean Ag(110)mentioning
confidence: 62%
“…However, without this step, it was difficult to achieve the desired separation of the 280 K peak from the molecular states in the vacuum system used for these experiments. Wu [3,5,9,24] generated strongly-bound oxametallacycle intermediates by ringopening epoxides on Ag surfaces and reported that activation of this process required adsorption at surface temperatures above 200 K; the oxametallacycles underwent ring-closure during TPD to reform the parent epoxides at temperatures well above those reported for desorption of the molecular epoxide states. The similar surface chemistry of the intermediate derived from ethylene oxide on Ag(110) to that of the oxametallacycle formed from ethylene oxide on Ag(111) suggests that the species formed on the Ag(110) surface is also an oxametallacycle.…”
Section: Ethylene Oxide Adsorption On Clean Ag(110)mentioning
confidence: 99%
See 3 more Smart Citations